الحقوق المالية للمرأة بين الضوابط الشرعية والممارسات العملية - إيمان غرايسة; حفصية غرايسة; نور الهدى مسعودي (University of Eloued-جامعة الوادي, 2018)
ىذه الدذكرة بعنواف: "الحقوؽ الدالية للمرأة بتُ الضوابط الشرعية كالدمارسات العملية" حيي دارت إشكالية ىذه الدذكرة حوؿ: ىل الدمارسة الدرأة لحقوقها الدالية ضمن ضوابط شرعية متفق عليها أ لا؟. كللإجابة على ىذا التساؤؿ الرئيسي سرنا كفق الخطة التالية: الدبحي الأكؿ كتضمن اةطار الدفاىيمي للحقوؽ الدالية للمرأة، أما الدبحي الثاني فكاف عن الضوابط الشرعية في التصرفات الدالية للمرأة أما الدبحي الثالي كالأختَ فكاف عبارة عن دراسة ميدانية تطبيقية عن طريق الاستبياف. كخلصت دراستنا إلى عدة نتائج منها أف للمرأة ذمة مالية مستقلة عن غتَىا، كلذا حرية التصرؼ في مالذا كلكن ضمن ضوابط شرعية متفق عليها. الكلمات المفتاحية: ضوابط حقوؽ ذمة لشارسة مالية شرعية. - - - - - Resume This subject is entitled women's financial rights be Abstract: This subject is entitled: Women's Financial Rights between Shari'a Controls and Practical Practices. Where the issue of this memorandum was about whether women exercise their financial rights within agreed legal controls or not. To answer this main question, we proceeded according to the following plan: The first section included the conceptual framework for the financial rights of women. The second topic was about the legal controls on the financial behavior of women, and the third and final subject was applied field study through the questionnaire. Our study concluded several results including: women has own financial obligation and have the freedom to dispose of her money, but within the agreed legal controls. Keywords: controls, rights, responsibility.
م\كرة ماستر
Keywords: حقوق /المراة /المالية/الضوابط الشرعية /الممارساتالعلمية; Droits / femmes / finance / contrôles juridiques / pratiques scientifiques